A MODERN DECONSTRUCTION OF THE ANCIENT MYTH OF MEDEA IN THE CREATIVITY OF GEORGIAN WRITERS (LASHA BUGHADZE "АНТИМЕДИЯ", PAATA TSIKOLIA'S "МЕДЕА S01E06") - Sigua, Lika (Journal of Learning on History and Social Sciences, 2024)
This paper explores the modern reinterpretation of the ancient myth of Medea, as presented by Georgian writers Lasha Bughadze and Paata Tsikolia. Despite the myth's ancient origins, its relevance persists in contemporary literature, where it reflects ongoing societal and existential conflicts. A knowledge gap exists in understanding how modern adaptations, particularly in Georgian literary contexts, reinterpret Medea's narrative using postmodern techniques. This study employs a comparative literary analysis method, examining plays like Bughadze's "Antimedea" and Tsikolia's "Медеа s01e06." Findings indicate that these works deconstruct traditional elements of the Medea myth, positioning the character within modern socio-political frameworks. The results reveal the use of irony, parody, and political symbolism to critique contemporary issues such as nationalism and gender roles. The implications of this study suggest that modern adaptations of ancient myths serve as powerful tools for addressing and re-evaluating current societal problems, particularly those related to identity and power dynamics.